Final Answer:
a. For the function f(x)=6x−2, f(2) = 10. b. Similarly, f(−2) = −14.
Step-by-step explanation:
To find f(2), substitute x=2 into the function f(x)=6x−2:
![\[ f(2) = 6 * 2 - 2 = 12 - 2 = 10. \]](https://img.qammunity.org/2024/formulas/mathematics/high-school/96fb7gbe7r7igr9edt6rpnau6qc9thqf8q.png)
So, the correct answer for part a is 10.
For f(−2), substitute x=−2 into the function:
![\[ f(-2) = 6 * (-2) - 2 = -12 - 2 = -14. \]](https://img.qammunity.org/2024/formulas/mathematics/high-school/qup6zmsz6dz51ayrxwwbby5n09f7wfyyvk.png)
Thus, the correct answer for part b is -14.
In summary, to evaluate the function at a specific value, substitute that value into the function expression. In this case, plugging in x=2 yields f(2) = 10, and substituting x=−2 gives f(−2) = −14. Understanding the process of substituting values into functions is fundamental to solving such problems and interpreting the behavior of mathematical functions.